The Relationship between Job Demands and Employees’ Counterproductive Work Behaviors: The Mediating Effect of Psychological Detachment and Job Anxiety - Chen, Yang; Li, Shuang; Xia, Qing; He, Chao (Frontiers in Psychology, 2017)
This study aims to explore the relation between job demands and counterproductive work behaviors. A cross-sectional sample of 439 coal miners completed a self-report questionnaire that assessed their job demands, psychological detachment, job anxiety, and counterproductive work behaviors in a Chinese context. The conceptual model, based on the stressor-detachment model, was examined using structural equation modeling. The results suggest that psychological detachment mediates not only the relation between job demands and job anxiety but also that between job demands and counterproductive work behaviors. Furthermore, the relation between job demands and counterproductive work behaviors is sequentially mediated by psychological detachment and job anxiety. Our findings validate the effectiveness of the stressor-detachment model. Moreover, we demonstrate that the underlying mechanism of the relation between job demands and counterproductive work behaviors can be explained by psychological detachment and job anxiety. Keywords: job demands, psychological detachment, job anxiety, counterproductive work behaviors, stressor-detachment model